PROFILE, KNOWLEDGE AND ADOPTION OF CRITICAL INTERVENTIONS OF MAJOR CROPS AMONG DRYLAND FARMERS IN PRAKASAM DISTRICT OF ANDHRA PRADESH - M. CHENNAMADHAVA; P.L.R.J. PRAVEENA (The Journal of Research ANGRAU, 2025)
The current study was conducted to examine the profile, knowledge, and adoption of key interventions among dryland farmers in the Prakasam district of Andhra Pradesh in 2021.An ex post facto research design was used for the study, and a sample of 120 dryland farmers was selected.The results revealed that most farmers were middle-aged (43.33%) or older (45%), with 31.67% being illiterate or having only primary or high school education. Small-scale farmers (56.66%) dominated, and land holdings had decreased due to family divisions. While a majority of farmers had medium (63.33%) to high (19.17%) farming experience, yields in redgram were low (37.5%) and medium in cotton (71.67%), primarily due to climatic challenges and limited irrigation. The majority (55%) had medium annual incomes, supplemented by livestock. Extension contact, media exposure, and information-seeking behaviors were generally medium, with farmers depending on local sources for advice, especially during droughts. Knowledge levels on farming interventions were predominantly medium to high, with 60% of farmers showing medium knowledge on redgram and 68.33% on cotton. Adoption rates were also moderate, with 63.33% adopting redgram interventions and 70% adopting cotton interventions to a medium extent. A significant correlation was found between farmers’ knowledge and adoption levels, with education playing a key role in both. Moreover, the study revealed a strong positive correlation between education and the adoption of improved farming practices for both crops. Key variables such as land holding, annual income, extension contact, and irrigation status were positively correlated with knowledge and adoption, while age and farming experience had negative correlations. The study emphasizes the need for targeted agricultural policies, enhanced extension services, and improved irrigation infrastructure to improve productivity and prevent rural-to-urban migration.